Aprender Windows Live con 100 ejercicios prácticos. (Colección Aprender (MEDIAactive (Firm)), 2010)
One hundred exercises give an overview of the Microsoft Windows Live Essentials suite of free software. Includes Windows Live Spaces, Windows Live Messenger, Windows Live Mail, Windows Live Writer, photo gallery, Movie Maker Beta, Windows Live Toolbar, Bing Maps, and Bing Translator.